Test items and standards related to muscle strength and endurance on the Brockport physical fitness test - Short, F. X.; Winnick, J. P. (Adapted Physical Activity Quarterly, 2005)
Testinhalte und -standards des Brockport Fitness-Tests bezüglich Kraft und Ausdauer.